Role of high-affinity HLA-DP specific CLIP-derived peptides in beryllium binding to the HLA-DPGlu69 berylliosis-associated molecules and presentation to beryllium-sensitized T cells - Amicosante, Massimo; Berretta, Floriana; Dweik, Raed; Saltini, Cesare (Immunology, 2009)
Berylliosis is driven by the accumulation in the lung of beryllium-specific T helper type 1 (Th1) cells recognizing beryllium as antigen when presented principally by human leucocyte antigen DP molecules carrying a glutamate at position β69 (HLA-DPGlu69). This study was designed to clarify the precise role of peptides in beryllium binding to the HLA-DP groove's pocket 4 and to identify peptides with higher affinity for pocket 4 that might prevent beryllium presentation and T-cell stimulation. Beryllium/HLA-DP interactions were analysed by the ability of beryllium to compete with CLIP and CLIP-derived peptides to HLA-DPGlu69 soluble molecule. The CLIP-derived low-affinity peptide CLIP-AA, could not outcompete beryllium; while the CLIP-derived high-affinity peptides CLIP-YY, CLIP-QY and CLIP-RF were only marginally influenced by the presence of beryllium in the competition assay. The effect of these CLIP-derived high-affinity peptides on beryllium presentation was determined by measuring interferon-γ (IFN-γ) release upon beryllium stimulation of peripheral blood mononuclear cells obtained from beryllium-hypersensitive subjects. CLIP-YY did inhibit beryllium presentation and T-cell activation, while CLIP-QY and CLIP-RF markedly enhanced the IFN-γ response to beryllium. Anti-HLA-DP monoclonal antibody blocked the beryllium-induced IFN-γ release in the presence of CLIP-QY (88%) and CLIP-RF (76%). A similar effect was observed for CLIP-YY capability to block IFN-γ release by beryllium stimulation in the presence of CLIP-QY (79%) and CLIP-RF (76%). Overall, these data support the proposal that HLA-DP high-affinity peptides might be used as a model for specific berylliosis therapy.